Illness perception of adolescents with allergic conditions under specialist care. Issue 2 (11th December 2019) - James, Polly; Caballero, Maria Rosario
Abstract: Background: Our understanding of how adolescents perceive and cope with their allergic condition/s is limited. This study used the Brief Illness Perception Questionnaire (BIPQ) in a group of adolescents with allergies and correlates the findings with demographic and clinical conditions. Methods: In this retrospective questionnaire‐based study, we analysed 100 valid questionnaires from adolescents (11‐18 years) attending our service after receiving management and treatment for their allergic condition/s. Results: The overall BIPQ score was 4.8 (IQR 3.6‐5.6). The highest item‐related scores were for "timeline" (illness duration) followed by "concern." The lowest scores were found for "coherence/understanding, " demonstrating that adolescents do not perceive that they have a sound understanding of their condition/s. We found a significant difference in the overall BIPQ scores between the genders and in the emotional representation score, with females showing a highest score. Older adolescents reported a more chronic perception of the allergic disease/s. Conclusion: Our results suggest that a better understanding and support of the allergic condition/s in adolescents, particularly in females, are likely an important target for intervention intended to improve their quality of life. BIPQ can be used as adjunct to routine allergy clinic appointments for further exploration of the wider impact of allergies on adolescents' lives. Abstract :